Sjogren-Larsson syndrome: A rare neurocutaneous disorder - Subramanian, Velusamy (J Pediatr Neurosci, 2016)
Sjogren-Larsson syndrome is an autosomal recessive disorder characterized by defective activity of fatty aldehyde dehydrogenase. It presents as a triad of congenital ichthyosis, spastic diplegia, and mental retardation. The pathology behind this syndrome is the failure of degradation of fatty aldehydes. This case is presented for its rarity.